Análise do efeito do Pronaf sobre a renda de agricultores familiares no meio rural nordestino - Sandro Pereira Silva; Juliane da Silva Ciríaco (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This research aims to investigate the effect of the National Program for the Strengthening of Family Agriculture (Pronaf) on income from work in rural Northeastern Brazil. For this purpose, data from the 2014 National Household Sample Survey (PNAD) were used and the propensity score matching (PSM) technique was applied. In general terms, the analyzes found show that the program provided an improvement in the income of agricultural work in the rural northeast. Estimates from the average treatment effect model showed that those who participate in Pronaf have an average income 29.3% higher compared to non-beneficiaries.
10419/284883
Keywords: R58; J38; Q19; 330; family farming; public policy; rural credit; impact assessment; income generation